Long-term visual, anterior and posterior corneal changes after crosslinking for progressive keratoconus. Issue 1 (January 2022) - Salman, Abdelrahman; Ali, Ali; Rafea, Shaaban; Omran, Rana; Kubaisi, Buraa; Ghabra, Marwan; Darwish, Taym
Aim: To evaluate the long-term outcomes of corneal cross-linking (CXL) in patients with progressive keratoconus. Method: In this retrospective non-comparative study, forty-five eyes of 31 patients with progressive keratoconus were treated with 30 min "epi-off" corneal cross-linking. The visual, refractive, topographic and tomographic outcomes were evaluated preoperatively and at least 10 years after cross-linking. Results: Ten years post-corneal cross-linking, the mean anterior maximum keratometry decreased (−2.10 ± 3.25 D, P = 0.0001). Conversely, the posterior maximum keratometry increased (6.38 ± 9.79 D, P = 0.065). Both uncorrected and corrected distance visual acuity improved (LogMAR −0.08 ± 0.30) and (LogMAR −0.05 ± 0.21), respectively (P > 0.05, both). A statistically significant hyperopic shift was observed postoperatively (0.70 ± 1.31 D, P = 0.0009). The anterior topographic cylinder values revealed no change (−0.17 ± 1.31 D, P = 0.3), whereas the mean posterior cylinder values decreased (absolute value increased) significantly compared to baseline from −1.31 ± 0.97 D to −1.82 ± 1.78 D, (P < 0.05). The minimum corneal thickness values decreased significantly (−35.11 ± 48.63 µm, P = 0.0001). Four eyes (8.8%) showed more than 1 D increase in the anterior maximum keratometry. Conclusion: This protocol and duration of Epi-off corneal cross-linking was found to be effective in halting keratoconus progression over the follow up period (10 years). Anterior corneal flattening and a hyperopic shift were observed. A statistically significant increase in the posterior corneal cylinder was observed. Although, not reaching statistical significance, the logMAR uncorrected and corrected visual acuity were improved.